DIGITAL SYSTEM UI/UX DESIGN MANAGEMENT SUBMISSION OF AGRICULTURAL COST LOANS USING FIGMA SOFTWARE - Sudjiran Sudjiran; Mohamad Saefudin; Safrido Ahmad Perdana (Journal of Information System, Informatics and Computing, 2023)
In the increasingly rapid development of technology, currently all the needs of our lives in various fields are slowly starting to penetrate the online (online)-based digital sector. One of them is related to capital lending and funding which is currently experiencing online-based development or known as Fintech (Finance Technology) and this technology is being widely used by the public, especially in Indonesia. Where, if we want to borrow capital or business funds, we can do it right away, simply by using an application/website platform that has been systemically designed, without having to come to a bank or cooperative. With the development of this technology, it is hoped that it will make it easier for the public to apply for loans of capital and funds in an efficient, effective and integrated manner between systems and humans.